Infection Can't be Hidden in a Pocket - I.V. Bogadelnikov; Ye.A. Kruger; A.V. Bobryshevа; G.I. Smirnov (Zaslavsky O.Yu., 2012)
The article deals with key aspects of infectious processes; brief description of cyclic, noncyclic and multi infectious processes that occur in the human body is given. The main points of immunological imprinting and the phenomenon of antibody-dependent enhancement of infection were summarized.